Kebijakan pajak dalam perdagangan melalui sistem elektronik: Mengupas pro dan kontra digital service tax - Destiny Wulandari (Directorate General of Taxes, 2024)
Amidst the massive spread of digital transactions, several countries impose DST (Digital Service Tax) on the gross revenue of digital enterprises instead of on profits. However, it causes pros and cons from an international point of view. This study aims to find a policy design for DST that can accommodate the pros and the cons. This study uses a narrative literature review of 20 pieces of literatures (national and international journals and conferences/proceedings) published in 2019 – 2023. By bringing together the pros and the cons, the results show that DST is applied as a swift response to the obsolete international taxation regime. Nevertheless, international consensus is still needed to overcome retaliation and to prevent double taxation that may happen due to DST enactment. The policy designs for DST that can be considered to accommodate the pros and the cons are the implementation of a threshold to determine tax subjects covered by international consensus and the treatment of DST as income deduction in residence jurisdiction. This implies that the policy design needs to be adjusted to accommodate the pros and cons of the enactment of DST so that it can be carried out based on the applicable taxation principles.